Controlled formation of coherent cuboidal nanoprecipitates in body-centered cubic high-entropy alloys based on Al2(Ni, Co, Fe, Cr)14 compositions. (1st April 2018) - Ma, Y.; Wang, Q.; Jiang, B.B.; Li, C.L.; Hao, J.M.; Li, X.N.; Dong, C.; Nieh, T.G.
Abstract: Microstructures and mechanical properties of Al-Ni-Co-Fe-Cr high-entropy alloys (HEAs) were investigated by systematically varying transition metals instead of Al, within the chemical formula of Al2 M14 (M represents different mutations of transition metals). The formation of different crystal structures (FCC, BCC, or FCC+BCC mixture) and its effects on the resulting mechanical properties of this series of HEAs, both in tension and compression, were evaluated. It was found that, in the BCC-dominated HEAs, ordered B2 precipitates were always coherently dispersed in the BCC solid-solution matrix. The shape of these B2 precipitates was strongly affected by the lattice misfit between the disordered BCC and ordered B2. A uniform distribution of cuboidal B2 particles could be obtained by properly adjusting M, thus the lattice misfit, in a manner similar to that in Ni-based superalloys. Strengthening effects caused by different BCC/B2 morphologies were also estimated and compared with experimental measurements. The optimal strengthening as a function of the shape and size of the coherent precipitates was discussed in light of the lattice misfit in these HEAs. Graphical abstract: Image 1